Today, urban planning engineering measures to protect the territory of Tashkent city from stormwater, urban planning analysis and solutions - Ph.D., Assoc. Usmonov Quvvat Turdiyevich; Orazbayeva Nazokat Maksetovna; Qosimov Zabixullo Xurillo o’g’li (Genius Journals, 2024)
In this article, the problems of water transfer systems in the cities of Uzbekistan are built on the example of the city of Tashkent. Possibilities of removing inconveniences caused by high-intensity precipitation of atmospheric water through existing drainage systems and the positive and negative aspects of using water drainage systems with the help of modern technologies in the world experience and their promotion in the territory of Uzbekistan were considered
Keywords: floods; torrents; surface water flows; sewage networks